Orange Bonds for Indonesia: A New Instrument to Drive Gender Equality and Sustainable Finance - Atmadjaja, Yovita Vivianty Indriadewi (International Journal of Social Science and Business, 2025)
This study highlights the structural disparities in women’s access to and participation in financial services and instruments as a core aspect of financial inclusion, which needs to be addressed through innovations such as Orange Bonds. Data shows that the majority of adult women do not have equal access to banking services. This reflects structural barriers that limit women's economic independence. The government needs to come up with innovative financial instruments that can bridge the gap. Orange Bonds are financial instruments that concurrently promote gender equality and sustainable development by financing women-focused empowerment initiatives alongside environmentally sustainable projects. This research aims to explore the role of Orange Bonds in supporting an inclusive and sustainable development agenda. The study examines the opportunities for Orange Bonds implementation in the context of regulatory, market, and social needs in Indonesia. The research used a qualitative approach with a combination of literature review, policy analysis, in-depth interviews, and thematic analysis. The results show that Orange Bonds can promote women's empowerment through access to training, business capital, and financial services. Government support, fiscal incentives, and cross-sector partnerships are considered important in strengthening the effectiveness of this instrument. The study concludes that Orange Bonds have the potential to be a strategic tool to achieve more equitable social and economic transformation. The research recommends strengthening regulations, developing gender equality indicators in investment policies, and improving public financial literacy as further steps. Periodic evaluations are suggested to ensure accountability and impact of funded programs. This research offers conceptual and practical contributions to the design of social justice-oriented financial instruments.